Urban agglomeration and CEO compensation - Bill Francis; Iftekhar Hasan; Kose John; Maya Waisman (Bank of Finland, 2012)
An underlying assumption in the executive compensation literature is that there is a national labor market for CEOs. The urban economics literature, however, documents higher ability among workers in large metropolitans, which results in a real and stable urban wage premium. In this paper, we investigate the link between the spatial clustering of firms in big, central cities (i.e., urban agglomeration) and the level and structure of CEO compensation. Using CEO compensation data for the period 1992-2004, we document a positive relation between the size and centrality of the city in which the firm is headquartered and the total, as well as the equity based portion of CEO pay. Our results are robust to a host of control variables, sensitivity and endogeneity tests, indicating that urban agglomeration may reflect positive externalities, such as knowledge spillovers, business connections and improved access to private information that have a positive effect on CEO pay and incentive driven compensation for good performance. We document gradual human capital gains acquired from big city work experience that are transferable to the rural area, and rewarded for, once the CEO relocates into a smaller, less central community. Our tests provide novel evidence of information spillovers and networking opportunities in big cities that can directly affect how CEOs are compensated. Such sources of information and influence represent something for which firms are willing to pay higher and more incentive driven pay, evidence in favor of a market-based explanation for CEO compensation.
URN:NBN:fi:bof-20140807651
Keywords: D8; G3; J3; R1; 330; Agglomeration; CEO; Compensation; Incentive; Geography